RANCANG BANGUN APLIKASI PENJUALAN OXYGEN PADA PT. SINAR PURNAMA SAKTI SEMARANG - Amalia Septi Reslili; Danang Danang (Pusat Riset dan Inovasi Nasional, 2024)
Sinar Purnama Sakti Semarang is an agent with a trading business that is engaged in the sale of Gas Oxygen (O2), Acyteline (C2H2), Carbondioxide (CO2) and Argon (Ar) experiencing problems, namely in the process of data processing sales of goods are still completely manual. This results in a good accumulation of transaction data, so that the efficiency and completeness of the data is not guaranteed. The purpose of this paper is to create an application that can help process data quickly and efficiently at PT. Sinar Purnama Sakti Semarang. This sales application is very helpful for users. With the new system in the sales application, it will make it easier to process data and make sales reports. In addition, PT. Sinar Purnama Sakti Semarang can also provide proof of payment in the form of a note. Performance of PT. Sinar Purnama Sakti Semarang becomes faster and more efficient after the sales application. So to simplify the sales information system is done with a computerized system. There are several programs that can be used in processing sales applications, one of which is the Visual Basic 6.0 program. Microsoft Visual Basic 6.0 is one of the most popular programs used in programming. Many people have used it and many people already know it. As for storage, the author uses Microsoft Office Access. Based on the description above, the authors take the title in accordance with the need for data processing information in PT. Sinar Purnama Sakti Semarang.